2012
DOI: 10.1164/rccm.201201-0164oc
|View full text |Cite
|
Sign up to set email alerts
|

Modern Age Pathology of Pulmonary Arterial Hypertension

Abstract: Rationale: The impact of modern treatments of pulmonary arterial hypertension (PAH) on pulmonary vascular pathology remains unknown. Objectives: To assess the spectrum of pulmonary vascular remodeling in the modern era of PAH medication. Methods: Assessment of pulmonary vascular remodeling and inflammation in 62 PAH and 28 control explanted lungs systematically sampled. Measurements and Main Results: Intima and intima plus media fractional thicknesses of pulmonary arteries were increased in the PAH group versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
353
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(375 citation statements)
references
References 20 publications
(7 reference statements)
17
353
2
3
Order By: Relevance
“…correlates with the disease severity, and in particular with pulmonary vascular wall remodelling and thickness [38,39]. Using neonatal, chronic hypoxia-induced PH models, FRID et al [40] found that pulmonary adventitial remodelling was due to the robust recruitment of monocyte/macrophage lineage cells expressing α-SMA that can produce collagen.…”
Section: Discussionmentioning
confidence: 99%
“…correlates with the disease severity, and in particular with pulmonary vascular wall remodelling and thickness [38,39]. Using neonatal, chronic hypoxia-induced PH models, FRID et al [40] found that pulmonary adventitial remodelling was due to the robust recruitment of monocyte/macrophage lineage cells expressing α-SMA that can produce collagen.…”
Section: Discussionmentioning
confidence: 99%
“…The perivascular infiltrate surrounding each pulmonary artery was quantified as follows: 0: absent, 1: minimal with a single layer clustering of inflammatory cells; 2: moderate, with localized clustering of inflammatory cells; and 3: abundant, with large clusters of inflammatory cells extending from the perivascular region toward adjacent alveoli. The final inflammatory score was the result of the following: [0 Â n vessels with 0 score þ 1 Â n vessels with score of 1 þ 2 Â n vessels with score of 2 þ 3 Â n vessels with score of 3]/number of analyzed vessels, as described elsewhere; 40 100 AE 36 vessels were examined per lung.…”
Section: Histology and Microscopymentioning
confidence: 99%
“…Circulating levels of serum cytokines including interleukin (IL)‐1β, IL‐2, IL‐4, IL‐6, IL‐8, IL‐10, IL‐12p70, and tumor necrosis factor α are significantly elevated when compared with controls 22, 23. IPAH shares a number of features with CHD‐APAH,24 and inflammation could develop in CHD‐APAH because of the high stresses associated with increased pulmonary blood flow and hypoxemia 25. Evidence of inflammation in CHD‐APAH includes inflammatory cell infiltrates around remodeled vessels,26, 27 and elevated circulating levels of IL‐6, tumor necrosis factor α,.MCP‐1, and C‐reactive protein have also been demonstrated 26, 27, 28…”
Section: Introductionmentioning
confidence: 99%